Determinants that affect usage intention on ChatGPT among university students in Malaysia - Ki, Yong Xi (2024)

(untitled)
This study aims to examine the determinants that influence usage intention on ChatGPT among university students in Malaysia by incorporating the Technology Acceptance Model (TAM). Meanwhile, Perceived Usefulness (PU), Perceived Ease of Use (PEoU), Perceived Trustworthiness (PT), and Perceived Personalization (PP) are the independent variables (IVs) of this study. These IVs employed to determine whether they could significantly influences the dependent variable (DV) – Intention to Use (INT) of ChatGPT. Apart from that, altogether 382 participants were collected as part of the data. Tool like Statistical Software Package for Social Sciences (SPSS) was utilized to evaluate the gathered data. Besides, the relationship between four IV and DV was illustrate using Internal Consistency Analysis such as Reliability Test, in addition to Inferential Analysis including Pearson Correlation Coefficient as well as Multiple Regression Analysis. Moreover, the study's findings had demonstrated that PU, PEoU, and PP have a significant impact toward the Intention to Use (INT) of ChatGPT, while PT has an insignificant influence toward the usage intention on ChatGPT.